Banco de dados do perfil químico e atividades biológicas dos óleos essenciais de espécies medicinais da região amazônica - Souza, Fabiana Silva de (Brasil, 2024)
Medicinal plants are important therapeutic tools capable of alleviating or curing illnesses, being of use and tradition of the population or community, endowed with pharmacological activities. The use of medicinal plants in the prevention and treatment of diseases is due to the presence of bioactive metabolites found in these plant drugs, reinforcing the possibility of these products reducing or causing side effects. Essential oils are natural, volatile substances, distilled from essences produced by plants. These substances can be found in flowers, leaves, stems, bark and roots. Essential oils are sources of natural substances that play an important role in acting as antibacterials, insecticides, anticancer, antioxidants and against herbivory. Among the botanical groups that stand out in the production of essential oils is the Piperaceae family, with immeasurable cultural and scientific value, housing a large number of species that have rich chemical composition. The Piper genus is the most representative of the Piperaceae family, highlighting, among other properties, its insecticidal potential. In addition to contributions in molecular biology, medicine, biotechnology and pharmacy. The Myrtaceae family is recognized for being used in numerous ethnopharmacological applications, such as hypoglycemic, hypotensive and antidiarrheal, as well as for having species that produce essential oils, which are of industrial, commercial and pharmacological importance. Some essential oils from native species of the Myrtaceae family from the Amazon biome have already been studied, with notable chemical diversity being observed. During the research it was observed that seasonality influences the chemical composition of the essential oil. Therefore, this work proposed to collect data on the essential oils of the Piperaceae and Myrtaceae family, as well as bibliographical research in the literature and organization of the database. The notebooks and records of the natural products research group for the period from 2008 to 2021 available at the Pharmacognosy Laboratory, at UFAM/ICET, were analyzed. Demonstrating that the biological activities tested against strains with oils from the Piperaceae and Myrtaceae family are promising for therapeutic purposes